Letter: questions regarding the diagnostic performance of serum assays for atrophic gastritis—Authors' reply. Issue 11 (3rd November 2017) - Zagari, R. M.; Greenwood, D. C.
Abstract : Linked Content This article is linked to Zagari et al and Graham papers. To view these articles visithttps://doi.org/10.1111/apt.14248 andhttps://doi.org/10.1111/apt.14339 .